Data from: 'Whale Wave': shifting strategies structure the complex use of critical fjord habitat by humpbacks ... - Keen, Eric M.; Wray, Janie; Meuter, Hermann; Thompson, Kim-Ly; Barlow, Jay P.; Picard, Chris R. (UC San Diego Library Digital Collections, 2017)
Using 10 years of whale surveys and a year of oceanographic, ecosystem-level surveying, we investigated the mechanisms behind a curious pattern in humpback whale (Megaptera novaeangliae) distribution, in which whales use a British Columbia fjord system in a kind of wave, propagating from offshore to inland channels as summer turned to fall. ...